Mentoring an Entrepreneur: Guide for a Mentor - Uddin, M.; Jamshed, Memon; M. Z. A., Rozan; Kamariah, Ismail; DzurllKanian, Daud (SAGE Publications, 2015)
A mentor plays an important role in entrepreneurial development of an individual. He guides entrepreneurs from conception of business to product development and business growth. Previous literature on entrepreneurial learning is disseminated and not properly organized; it is difficult to even find pertinent and comprehensive articles on entrepreneurial learning. The research proposed in this article helps mentors to understand and find out what type of entrepreneurs need what kind of mentoring support. This article proposes a conceptual model for mentors and discusses that an entrepreneur may need different mentoring support and skills depending on the type of entrepreneurs, personality traits, or decision-making style and phase at which entrepreneurs are at that moment. This article will also help mentors in understanding what type of skills entrepreneurs need at each stage of mentoring relationship, that is, initiation, cultivation, separation, and redefinition stage.